Pursuer-evasion strategy optimisation in air combat scenarios - Nusyirwan, Istas F. (2007)
Pursuit-evasion (variants of which are referred to as cops and robbers and graph searching) is a family of problems in mathematics and computer science in which one group attempts to track down members of another group in an environment. Early work on problems of this type modeled the environment geometrically.